Implementation of STEM-PjBL Teaching Materials to Improve Student Learning Outcomes and Interest in Acid-Base Topics - Citra Permata Sari Sinaga; Susilawati Amdayani (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Although STEM-integrated Project-Based Learning (PjBL) has been widely examined for its effects on individual learning dimensions, no comparative study has simultaneously investigated its differential impact on both cognitive learning outcomes and affective learning interest using a two-class experimental design in Indonesian secondary chemistry education, particularly for the acid-base topic. Existing studies are further limited by single-variable focus, short-term self-report instruments, and a lack of multi-project STEM designs that integrate cross-disciplinary engineering and mathematical reasoning alongside scientific inquiry. This study addresses these gaps by implementing a STEM-PjBL e-module featuring three differentiated cross-disciplinary projects and comparing its effects against a conventional textbook-based PjBL class. A quasi-experimental pretest-posttest design was employed at SMAN 1 Panombeian Panei during the even semester of the 2025/2026 academic year, with a four-meeting intervention (2 × 45 minutes each). The sample comprised 60 students: 30 in Experimental Class 1 (STEM-PjBL e-module) and 30 in Experimental Class 2 (textbook + PjBL). Within the context of this study, Experimental Class 1 achieved a mean posttest of 80.50 (N-Gain = 0.521, moderate), while Experimental Class 2 achieved 66.00 (N-Gain = 0.266, low). Learning interest in Class 1 increased from 64% to 82% (+18%), compared to 61% to 77% (+16%) in Class 2. Independent Sample t-tests indicated significant differences in outcomes (sig. = 0.000) and interest (sig. = 0.033). Pearson correlation revealed a strong positive association (r = 0.789, sig. = 0.000). These findings suggest that, within this specific context, STEM-PjBL teaching materials with a multi-project design may provide greater pedagogical benefits than conventional textbook-based PjBL.